The Dissolution of Political Parties as Sanctions for Corruption Crimes - Alwi Yusup Ramadhan; Muhammad Dzikri A. S; Irsyad Ilyas T; Yuliant Prajaghupta (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
This study delves into the corporate criminal responsibility of political parties in cases of corruption and money laundering committed by their members. The intricacy lies in the challenge of attributing individual actions within political parties to the parties themselves. The primary concern investigated is the application of the dissolution sanction for political parties proven to engage in criminal acts of corruption and money laundering as a manifestation of their criminal responsibility. Employing a statutory, analytical, and conceptual approach, the research draws on legal materials derived from secondary data, encompassing primary, secondary, and tertiary legal sources. The findings reveal that the Constitutional Court possesses the authority to dissolve a political party as a corporate entity. The decision rendered by the District Court Judge serves as a pivotal reference for the government, facilitated through the attorney general and/or the appointed Minister by the President, to submit a dissolution request to the Constitutional Court. The actual execution of the dissolution rests within the purview of the Constitutional Court, aligning with its designated authority. This study sheds light on the intricate legal mechanisms surrounding the corporate criminal responsibility of political parties and underscores the role of the Constitutional Court in addressing such cases.